A Numerical Analysis of Wind Flow in Urban Areas - Kim Dung Hoang, Thi; Nguyen, Phu Khanh (IPTEK Journal of Proceedings Series, 2017)
The high population density in Vietnam create many challenges in its urban development and supply of residential housing. To accommodate the large population, the buildings tend to go vertical and high density to maximize the development ratio in the limited land space and in the conservation of natural geomorphology. The high density of building blocks reduces the permeability for wind penetration. In the extreme case, the housing estate becomes a wind-obstructing structure that could be causing to environmental problems and health hazard due to low level of ventilation follow. So, a better understanding about wind flow in urban areas could help resolve some of the main difficulties that a designer might encounter to improve the geometries of urban areas. Therefore, this article performs the simulation methodology using Computational Fluid Dynamics (CFD) tools in ANSYS FLUENT software to carry out the urban wind environment in the simple planning and design urban areas. The studied parameters were wind velocity 10 m/s in the case of straight wind and in the case of 450-cross wind. CFD is an effective and efficient tool to visualize a flow phenomenon of a particular flow problem. The advanced computational technique could calculate the fluid properties at all points defined within the model domain, providing a complete set of data within the model. However, it is important to highlight that CFD technologies have not been completely reliable as model assumptions are still unavoidable for the present computational technologies to resolve turbulent flows. Understanding the limitations of CFD is crucial to reduce numerical errors and realize possible erroneous data in the model.